Crisis Management of North Lombok District Government Public Relations During The Lombok Earthquake In 2018 - Nadya Ulfa; I Wayan Suadnya; Hartin Nur Khusnia (Universitas Mataram, 2019)
North Lombok District is the worst affected area by the Lombok earthquake in 2018. Many hoaxes spread, even demonstration for demanded stimulus fund during disaster management. It could affect public trust in North Lombok District government. Therefore, North Lombok District government need Public Relations to manage communication crisis. The purpose of this research is to know the crisis management of North Lombok government Public Relations during the Lombok earthquake in 2018. The type of this study is qualitative research with descriptive analysis. The result of this study show that North Lombok District Government Public Relations only respond to crisis according to the situation and conditions. It caused by they do not have a crisis communication plan before. The command post formed to effectively coordinate. Public Relations is more involved in information management activities. Analysis of public information is used as input and evaluation. After crisis, Public Relations formulated a long term plan to build the image of North Lombok government as the disaster resilient district. Keywords: Crisis management; Government Public Relations;The Lombok Earthquake